Norms and the Study of Language in Social Life - Coupland, Nikolas; Fabricius, Anne; Harder, Peter; Hazel, Spencer; Holmes, Janet; Kraft, Kamilla; Lønsmann, Dorte; Marra, Meredith; Mortensen, Janus; Piippo, Irina; Pitzl, Marie-Luise; Vine, Bernadette (Language and Social Life [LSL] ,, 2022)
Sociolinguistics and the social sciences more generally tend to take an interest in norms as central to social life. The importance of norms is easily discernible in the sociolinguistic canon, for instance in Labov's definition of the speech community as 'participation in a set of shared norms' and Hymes' concepts of 'norms of interaction' and 'norms of interpretation'. Yet, while the notion of norms may play a central role in sociolinguistic theory, there is little explicit theoretical work around the notion of norms itself within the discipline. Instead, norms tend to be treated as conceptual primes - convenient building blocks, ready-made for sociolinguistic theorizing - rather than theoretical constructs in need of reflexive attention. The aim of this book is to assess and advance current understandings of norms as a theoretical construct and empirical object of research in the study of language in social life. The contributors approach the topic from a range of complementary disciplinary perspectives, including sociolinguistics, linguistic anthropology, EM/CA, socio-cognitive linguistics and pragmatics, to provide a multifaceted view of norms as a central concept in the study of language in social life.